Development and Validation of a Novel Predictive Model for the Early Differentiation of Cardiac and Non-Cardiac Syncope - Wu S; Chen Z; Gao Y; Shu S; Chen F; Wu Y; Dai Y; Zhang S; Chen K (International Journal of General Medicine, 2024)
Sijin Wu,1 Zhongli Chen,1 Yuan Gao,1 Songren Shu,2 Feng Chen,1 Ying Wu,1 Yan Dai,1 Shu Zhang,1 Keping Chen1 1Arrhythmia Center, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Cardiovascular Surgery, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of ChinaCorrespondence: Keping Chen, Arrhythmia Center, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences & Peking Union Medical College, 167 Beilishi Road, Xicheng District, Beijing, 100037, People’s Republic of China, Email chenkeping@263.netBackground: The diagnosis of cardiac syncope remains a challenge. This study sought to develop and validate a diagnostic model for the early identification of individuals likely to have a cardiac cause.Methods: 877 syncope patients with a determined cause were retrospectively enrolled at a tertiary heart center. They were randomly divided into the training set and validation set at a 7:3 ratio. We analyzed the demographic information, medical history, laboratory tests, electrocardiogram, and echocardiogram by the least absolute shrinkage and selection operator (LASSO) regression for selection of key features. Then a multivariable logistic regression analysis was performed to identify independent predictors and construct a diagnostic model. The receiver operating characteristic curves, area under the curve (AUC), calibration curves, and decision curve analysis were used to evaluate the predictive accuracy and clinical value of this nomogram.Results: Five independent predictors for cardiac syncope were selected: BMI (OR 1.088; 95% CI 1.022– 1.158; P =0.008), chest symptoms preceding syncope (OR 5.251; 95% CI 3.326– 8.288; P < 0.001), logarithmic NT-proBNP (OR 1.463; 95% CI 1.240– 1.727; P < 0.001), left ventricular ejection fraction (OR 0.940; 95% CI 0.908– 0.973; P < 0.001), and abnormal electrocardiogram (OR 6.171; 95% CI 3.966– 9.600; P < 0.001). Subsequently, a nomogram based on a multivariate logistic regression model was developed and validated, yielding AUC of 0.873 (95% CI 0.845– 0.902) and 0.856 (95% CI 0.809– 0.903), respectively. The calibration curves showcased the nomogram’s reasonable calibration, and the decision curve analysis demonstrated good clinical utility.Conclusion: A diagnostic tool providing individualized probability predictions for cardiac syncope was developed and validated, which may potentially serve as an effective tool to facilitate early identification of such patients.Keywords: cardiac syncope, syncope, diagnosis, nomogram, prediction model